2021
DOI: 10.1002/ejhf.2263
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hospital transfer to hubs on outcomes of cardiogenic shock in the real world

Abstract: Cardiogenic shock (CS) is associated with significant mortality, and there is a movement towards regional 'hub-and-spoke' triage systems to coordinate care and resources. Limited data exist on outcomes of patients treated at CS transfer hubs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…In terms of clinical utility for clinical practice, a risk score model would ideally inform clinical decision‐making ( Figure ). The risk score should help to efficiently triage ‘selected patients’ to an appropriate care location, from ‘spoke’ to ‘hub’ hospitals, in order to facilitate specific interventions tailored to the aetiology and severity of CS 18,19 . Transferring patients who are too sick or out of the window of benefit may be futile, 4,18 while careful selection for transfer of targeted patients who may be potentially candidates for advanced therapies, may contribute to better outcomes.…”
Section: Figurementioning
confidence: 99%
“…In terms of clinical utility for clinical practice, a risk score model would ideally inform clinical decision‐making ( Figure ). The risk score should help to efficiently triage ‘selected patients’ to an appropriate care location, from ‘spoke’ to ‘hub’ hospitals, in order to facilitate specific interventions tailored to the aetiology and severity of CS 18,19 . Transferring patients who are too sick or out of the window of benefit may be futile, 4,18 while careful selection for transfer of targeted patients who may be potentially candidates for advanced therapies, may contribute to better outcomes.…”
Section: Figurementioning
confidence: 99%
“…However, in spite of limitations, the results of the current research suggest a clear signal of survival benefit for these critically ill patients when referred to a CS network with appropriate organization in terms of facilities, staff allocation, expertise and standardized protocols. Frequent training and quality improvement should be incorporated into CS teams to sustain adequate clinical and procedural proficiency 6,8 . Although, an accepted threshold for cost‐effectiveness has not been ‘politically specified’, the extensive resources needed to maintain CS teams require constant institutional administrative support, sufficient funding and staffing, and continuous documentation by cost‐effective analysis 6 .…”
Section: Figurementioning
confidence: 99%
“…Despite lower mortality, CS patients directly admitted or transferred to hub hospital had longer lengths of stay, higher rates of procedural-related complications such as major bleeding, stroke, vascular complications and acute kidney injury (AKI), and finally higher costs and higher 30-day readmissions. 8 In multivariable analysis, direct admission to a hub hospital [odds ratio (OR) 0.86, 95% confidence interval (CI) 0.84-0.89] and interhospital transfer to a hub hospital (OR 0.72, 95% CI 0.69-0.76), revascularization with PCI or CABG and use of RHC were independently associated with significantly lower mortality. In contrast, MCS use and other index admission characteristics, such as acute myocardial infarction (AMI), cardiac arrest, mechanical ventilation, and AKI requiring dialysis, were associated with significantly higher mortality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…showed that a regional 'hub-and-spoke' triage system, with direct admission to CS hubs or transfer to hubs, is associated with a lower mortality. 27 Mechanical circulatory support (MCS) may be useful in the management of CS. 26 However, data from randomized controlled trials (RCTs) seem not to reflect real-world practice.…”
Section: Cardiogenic Shockmentioning
confidence: 99%